Pendekatan Holistik untuk Meningkat Kualitas Hidup Pasien Tuberkulosis Paru di RSUD Ende - Yustina Paschalia (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) is a contagious infectious disease that is one of the leading causes of death worldwide after HIV. Based on WHO reports, it is estimated that there are 10,600,000 cases of tuberculosis globally with a mortality rate of 1,400,000 cases. The purpose of this study is to improve the quality of life of Mr. MKE with a medical diagnosis of pulmonary tuberculosis at the RPK RSUD Ende. The method used is a case study with a nursing care approach. The results of Mr. MKE's assessment found that the patient said he was a little short of breath, coughing up thick yellow phlegm, sometimes greenish, which sometimes can be expelled, sometimes difficult to expel since ± 4 months. Pain in the right side of the chest when coughing, fever that goes up and down for + one month, dizziness when getting out of bed, weak, limp. Decreased appetite, nausea, vomiting, eating 5 times a day, the portion consumed is only + 2-3 spoons, sweating at night without doing any activity, previous weight: 60 kg. Physical activities such as getting out of bed, moving, etc. are assisted by the family. Hb 6 gr/dl. Nursing problems found were ineffective airway clearance; hyperthermia; nutritional deficits; ineffective peripheral perfusion; Activity intolerance; ineffective health management. After 3x24 hours of care and treatment, the results showed that ineffective airway clearance was partially resolved, hyperthermia was resolved, nutritional deficits were partially resolved, ineffective peripheral perfusion was resolved, activity intolerance was partially resolved, and ineffective health management was resolved. This is expected to improve the patient's quality of life. It is recommended that patients and their families follow all recommendations from doctors and nurses with the aim of accelerating the patient's healing process.